Comparative Study Of Maryam's Storytelling In Ibn Kathir's Tafseer And Sibel Eraslan's Siret-i Meryem (Cennet Kadınların Sultanı): Studi Komparasi Penyampaian Kisah Maryam dalam Tafsir Ibnu Katsir dan Novel Siret-i Meryem (Cennet Kadınlarının Sultanı) Karya Sibel Eraslan - Sulthoni, Akhmad; Khairi, Shohib; Muttaqin, Kholil (Civilization Research: Journal of Islamic Studies, 2025)
This research aims to comparatively analyze the presentation of Maryam’s story in Tafsir Ibn Kathir and the novel by Sibel Eraslan, identifying their similarities and differences. The methodology employed is library research with a descriptive-analytical approach. Data analysis was conducted using comparative methods to evaluate the elements of characters, plot, setting, and narrative style. The findings indicate that Tafsir Ibn Kathir presents Maryam’s story based on authentic narrations with a scholarly approach emphasizing the accuracy of sources. Conversely, Sibel Eraslan’s novel incorporates fictional elements into the characters, plot, and setting, with a literary style aimed at evoking emotional responses from readers. Both share similarities in the core story of Maryam but differ in their narrative enrichments: Tafsir Ibn Kathir highlights scholarly and spiritual aspects, whereas Sibel Eraslan’s work offers emotional and aesthetic nuances. The implications of this study underscore the importance of understanding the boundaries between religious texts and creative interpretations in literary works. These findings contribute to the development of interdisciplinary studies between Qur'anic exegesis and contemporary literature, enriching the dialogue between scholarly traditions and creative arts.